Peranan Sanggar Watu Bo dalam Produksi Tenun Ikat Tradisional Desa Kajowair - Marlini, Sisilia; Murniasih, A.A. Ayu; Kaler, I Ketut (Humanis; Vol 24 No 3 (2020)DO - 10.24843/JH.2020.v24.i03.p11, 2020)
Watu Bo institut server as  container of eduction and preserves by reproducing traditional woven cloth passed down from the ancestor using natural substance and dyes as well traditional loom loms, not machines (ATMB). The problem formula in this research covers (1) how was the traditional binding processin the Watu Bo Workshop?, (2) what is the Watu Bo’s strategic role in the existence of traditional Weaving?.  As for the purpose of this study is (1) to know the traditional weaving works in the Watu Bo  cage. (2) to identify Watu Bo’s strategic role against traditional weaving.The theory used in the study, the theory of production and the theory of role, because weavers in  Watu Bo  industries play a part in this traditional weaving work. But among the concepts that are used: roles, Watu Bo cage, and the production of zip looms. In this study the method in use is qualitative descriptive, with primary and secondary data sources, with data collection techniques through observation, interviews, and library studies.Results found in studies suggest that a Watu Bo clinic produces traditional weaving, using natural materials and dyes and using loom equipment instead of maschines to produce  colth. Production products are sold booth local and foregin communities. Watu Bo’s  cage plays strategic role in the traditional weaving of weaving; help to boots the family economy, preserving cultural heritage, passing on the rising generation, absorbing the peach of work, tourism, and helping to preserve the environment